Kebebasan Beragama dan Hak Asasi Manusia: Studi Komparatif Ajaran Islam, Kristen, dan Hindu - Maryam Rasyid; Ahmad Malikai; Alexsander Bani; I Gede Febriyasa (Yayasan Albahriah Jamiah Indonesia, 2025)
Freedom of religion is a central issue in human rights discourse, yet it still faces serious challenges in the form of increasing intolerance and belief-based violence. Although the literature on each religious tradition is quite extensive, a notable lack remains in studies that systematically compare the theological foundations and normative implications of Islamic, Christian, and Hindu teachings with modern standards of religious freedom, thereby creating a conceptual gap in the study of religion and human rights. This study aims to describe the key doctrines of the three traditions regarding freedom of belief, compare the normative principles governing the relationship between individual freedom and religious authority, and identify conceptual points of convergence and differences in relation to universal human rights principles. The method used is a qualitative-comparative study with hermeneutic textual analysis of primary sources, namely the Quran, the Bible, and the Vedas, based on thematic relevance, as well as a review of purposively selected secondary academic literature. Data were analyzed using a thematic analysis approach to map conceptual patterns across traditions. The results of the study reveal four main themes: first, the theological basis of freedom of belief; second, the moral and social limits of individual freedom; third, the position of religious authority; and fourth, the relationship between tolerance and pluralism. Islam emphasizes freedom oriented toward moral responsibility and social justice; Christianity emphasizes freedom of conscience based on the dignity of the imago Dei. In contrast, Hinduism emphasizes spiritual plurality as a space for seeking truth. All three demonstrate a consensus on human dignity and the rejection of coercion. The focus of the textual analysis limits the conclusions; empirical studies are needed to test their implementation in social practice and public policy.